An elastic stability-based method to predict the homogenized hoop elastic moduli of reinforced thermoplastic pipes (RTPs). (15th December 2019) - Liu, Wencheng; Wang, Shuqing
Abstract: The homogenized hoop elastic moduli are key parameters of RTPs that must be considered in the buckling collapse predictions and pipe designs. However, it is difficult to give an accurate analytical solution due to the material anisotropy of RTPs. To address this problem, a novel method is proposed based on the classical elastic stability theory and NASA SP-8007 formula. This method is under the assumption that the critical pressures of homogenized RTPs equal the critical pressures calculated by the classical lamination theory and Donnell-type stability differential equations. One advantage of this method is that it could simultaneously consider the extensional response, the bending response, and the extensional-bending coupling response of laminates in the calculation of homogenized hoop elastic moduli. Meanwhile, it gives a more concise formula form and doesn't involve successive iterations in comparison with the existing homogenization method. Numerical simulations of the crushing case were used to verify the effectiveness of the proposed method. Compared with numerical results and the existing homogenization method, the proposed method was found to give accurate results. Furthermore, the effects of fiber's winding angles and thickness-radius ratios, and the proportional relations between the homogenized hoop elastic moduli and the reciprocal of radii were investigated.